2017
DOI: 10.3390/s17030554
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodality Hybrid Gamma-Optical Camera for Intraoperative Imaging

Abstract: The development of low profile gamma-ray detectors has encouraged the production of small field of view (SFOV) hand-held imaging devices for use at the patient bedside and in operating theatres. Early development of these SFOV cameras was focussed on a single modality—gamma ray imaging. Recently, a hybrid system—gamma plus optical imaging—has been developed. This combination of optical and gamma cameras enables high spatial resolution multi-modal imaging, giving a superimposed scintigraphic and optical image. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Although the integration of modalities was shown to be synergistic, this study also demonstrated the extent of hardware developments needed to produce a truly integrated system—matched FOVs at a range of imaging distances, adjustable focus for each imaging distance without interrupting surgical workflow and the need to improve the sensitivity of NIR fluorescence imaging at larger imaging distances through improved camera sensitivity and higher powered excitation light sources [ 39 ]. Technologies designed for combined gamma–visible imaging (see “ Gamma–bright field imaging ”) show that the coalignment of these modalities is achievable (as the principles behind visible and NIR fluorescence detection are identical)—recently, an adaptation to the Hybrid Gamma Camera has been tested to show proof of concept simultaneous co-aligned gamma–NIR fluorescence imaging [ 75 ]; however it is not known whether the required sensitivity in NIR fluorescence would be achievable with this system.…”
Section: Resultsmentioning
confidence: 99%
“…Although the integration of modalities was shown to be synergistic, this study also demonstrated the extent of hardware developments needed to produce a truly integrated system—matched FOVs at a range of imaging distances, adjustable focus for each imaging distance without interrupting surgical workflow and the need to improve the sensitivity of NIR fluorescence imaging at larger imaging distances through improved camera sensitivity and higher powered excitation light sources [ 39 ]. Technologies designed for combined gamma–visible imaging (see “ Gamma–bright field imaging ”) show that the coalignment of these modalities is achievable (as the principles behind visible and NIR fluorescence detection are identical)—recently, an adaptation to the Hybrid Gamma Camera has been tested to show proof of concept simultaneous co-aligned gamma–NIR fluorescence imaging [ 75 ]; however it is not known whether the required sensitivity in NIR fluorescence would be achievable with this system.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the in-depth information of radioguidance provided the ability to more accurately position the fluorescence camera. A portable and fully integrated hybrid γ and fluorescence camera has only been studied in preclinical evaluations [223]. In this system, γ and fluorescent emissions are both collected at the front of the device, but in the camera are separated through an angled mirror (45°) to allow for separate detection.…”
Section: Background and Recent Advances Fluorescencementioning
confidence: 99%
“…A variety of these systems is currently commercially available for MIGS (Supplemental Table 3). These devices are generally less expensive than the standalone systems and provide an intuitive user experience (21,(25)(26)(27). However, the system does not support hands-free surgery, implying that the operation will stop when the system is used by the operating surgeon.…”
Section: Handheldmentioning
confidence: 99%
“…Design configurations for molecular image-guided surgical devices, including standalone(22), handheld(25), wearable (arrow) (28), minimally invasive(30), and robotic(36).…”
mentioning
confidence: 99%